Immunisation of immunocompromised children against pneumococcus: which vaccine should now be used?. (29th September 2015) - Finn, A; Dymond, S; Findlow, J; Webb, N; Nagra, A; Borrow, R; McGraw, M
Abstract : Although efficacy has never been demonstrated in children, 23-valent pneumococcal vaccine (PPV23) consisting of multiple unconjugated capsular polysaccharides has long been recommended for many children in high risk groups. Even since licensure of lower valency conjugated vaccines for which efficacy data are strong, PPV23 has continued to be recommended as part of a combined schedule and for children aged >5 years. Children with chronic renal diseases are representative of broader high risk groups having susceptibility both related to primary disease and immunosuppressive treatment. The authors immunised PCV7-naïve children with seven valent conjugate vaccine (PCV7) and 6 m later with a test dose (0.1 ml) of 23valent polysaccharide vaccine (challenge). Serum was collected immediately before (V1 and V3) and 28–42 days after (V2 and V4) each vaccine dose and assayed (Luminex bead) for IgG antibody to PCV7 serotypes (ST). 75 children (51 male) aged 2.6–18.7 years (mean 11.5) were enrolled in three UK centres. 42 were post-renal transplant and 19 had chronic renal failure, of whom eight were on renal replacement therapy and two were awaiting transplant. Two had glomerulonephritis with low C3 and/or C4 and 14 had nephrotic syndrome that was steroid resistant and/or frequently relapsing. Geometric mean concentrations (n=55, μg/ml) at the four study visits (V) are shown in the table. Serum antibody responses to PCV7 showed mean 14.1-fold rises (range 5.8–19.1 for the seven serotypes). 75% (ST4) to 88% (STs 18C and 23F) achieved serum concentrations ≥0.35 μg/ml. After falling to mean 0.5 of post immunisation, a mean twofold titre rise (range 1.5–2.4) occurred after challenge, suggesting immunological memory. Children (n=10) who had received PPV23 prior to the study had much lower responses to PCV7 (p=0.01) suggesting hyporesponsiveness but had similar fold-rises (p=0.52) on PPV23 challenge. PCV7 was highly immunogenic in these immunocompromised children. These results confirm that, after inducing short-lived antibody responses, PPV23 induces hyporesponsiveness to pneumococcal antigens. With the availability of 10- and 13-valent conjugate vaccines, in the absence of evidence of benefit and in the presence of evidence of potential harm, consideration should now be given to cessation of use of PPV23 in childhood.